(untitled) (Revista cientifica In Vestigium Ire, 2020)
Duitama has 20 aqueducts sidewalk, providing water supply services to 5,616 users, who otherwise would not be able to count on this vital resource, given its rural location. The aim is to describe the current situation of the 20 veredales aqueducts legally constituted and registered in the Duitama City Hall, from the perspective of governance, quality and performance. The results obtained allow us to establish that if these aqueducts continue with their current financial and operational management, they will not be viable in time. It is important to highlight the role that these communities play, which is fundamental to ensure water supply to the non-covered sectors, and it is also imperative not to lose sight of the fact that these social and operational dynamics are contributing to improving the quality of life of the inhabitants of Duitama, but they require differential schemes in their regulations that guarantee sustainability over time.